Collective Control of Potential-Constrained Oxygen Vacancies in Oxide Heterostructures for Gradual Resistive Switching - Jeon, Jaeyoung; Eom, Kitae; Lee, Minkyung; Kim, Sungkyu; Lee, Hyungwoo (Small, 2023)
Filamentary resistive switching in oxides is one of the key strategies for developing next-generation non-volatile memory devices. However, despite numerous advantages, their practical applications in neuromorphic computing are still limited due to non-uniform and indeterministic switching behavior. Given the inherent stochasticity of point defect migration, the pursuit of reliable switching likely demands an innovative approach. Herein, a collective control of oxygen vacancies is introduced in LaAlO3/SrTiO3 (LAO/STO) heterostructures to achieve reliable and gradual resistive switching. By exploiting an electrostatic potential constraint in ultrathin LAO/STO heterostructures, the formation of conducting filaments is suppressed, but instead precisely control the concentration of oxygen vacancies. Since the conductance of the LAO/STO device is governed by the ensemble concentration of oxygen vacancies, not their individual probabilistic migrations, the resistive switching is more uniform and deterministic compared to conventional filamentary devices. It provides direct evidence for the collective control of oxygen vacancies by spectral noise analysis and modeling by Monte-Carlo simulation. As a proof of concept, the significantly-improved analog switching performance of the filament-free LAO/STO devices is demonstrated, revealing potential for neuromorphic applications. The results establish an approach to store information by point defect concentration, akin to biological ionic channels, for enhancing switching characteristics of oxide materials.
Keywords: Collective control; Filament-free; LaAlO 3; Neuromorphic computing; Non-uniform; Nonvolatile memory devices; Oxide heterostructures; Resistive switching; SrTiO 3; Switching behaviors; collective control; filament-free; oxide heterostructures; oxygen vacancies; resistive switching